Laser-driven self-exfoliation of graphene oxide layers on a fiber facet for Q switching of an Er-doped fiber laser at the longest wavelength - Kim, Byungjoo; Hong, Seongjin; Park, Jaedeok; Lee, Yongsoo; Yeom, Dong Il; Oh, Kyunghwan (Photonics Research, 2020)
A new method to make an all-fiber nonlinear optic device for laser pulse generation is developed by depositing multi-layer graphene oxide (GO) selectively onto the core of the cleaved fiber facet by combining the electrical arc discharge and the laser-driven self-exfoliation. Using the GO colloid droplet with sub-nanoliter volume, we obtained a GO bulk layer deposited on a fiber facet of the order of milliseconds by using an electric arc. The prepared fiber facet was then included in an Er-doped fiber laser (EDFL) cavity and we obtained a few layers of GO having nonlinear optic two-dimensional (2D) characteristics selectively on the fiber core by the laser-driven self-exfoliation. The 2D GO layers on the fiber core served as a stable and efficient saturable absorber enabling robust pulse train generation at λ = 1600.5 nm, the longest Q-switched laser wavelength in EDFLs. Pulse characteristics were analyzed as we varied the pump power at λ = 980 nm from 105.2mW to 193.6 mW, to obtain the maximum repetition rate of 17.8 kHz and the maximum output power of 2.3 mW with the minimum pulse duration of 7.8 μs. The proposed method could be further applied to other novel inorganic 2D materials opening a window to explore their novel nonlinear optic laser applications.
Keywords: Er-doped fiber laser; Maximum output power; Pulse characteristics; Pulse durations; Pulse generation; Pulse-train generation; Repetition rate; Two Dimensional (2 D)